Analisis Emisi Karbon Pada Material Bangunan Gedung Tujuh Lantai dengan Metode BIM - Adeis Trisa Pihawiano; Subrata Aditama; Lendra; Waluyo Nuswantoro (Jurnal Serambi Engineering, 2024)
The city of Palangka Raya, Central Kalimantan is a green city that has many high-rise buildings which are at risk of producing large amounts of carbon emissions, due to the use of building materials that are not environmentally friendly. This condition will get worse with theincreasing number of high-rise buildings that will be built in the future if they do not use environmentally friendly materials. This research aims to find out the amount of carbon emissions in the structural materials of multi-storey buildings. The research begins by carrying out 3D modeling using Tekla Structure Software, then specification information and work volume from the modeling results will be used to calculate the value of carbon emissions in building materials using coefficients from the Inventory Of Carbon And Energy from the University of Bath journal. The research results show that there are 16 materials that produce carbon emissions and have 2 dominant materials that produce carbon emissions, namely the Cement Plaster material which is the material that has the largest carbon emission value with a contribution of carbon emission value of 349,000.954 kgCo2/Kg (48.092%) then Iron material with a value of 339,035.037 kgCo2/Kg (46.718%)